The Use of Organophosphate and Carbamate Pesticides on Paddy Fields and Cholinesterase Levels of Farmers in Sam Chuk District, Suphan Buri Province, Thailand - Duangchinda, Aittiphol; Anurugsa, Bundit; Hungspreug, Natha (Science & Technology Asia, 2014)
Several types of organophosphate and carbamate pesticides have been used extensively by the farmers in Thailand during the last few decades. This study examines the use of organophosphate and carbamate pesticides and cholinesterase levels in the blood (AChE) of farmers by using reactive paper on samples which were taken from 236 farmers in Sam Chuk district, Suphan Buri province. Moreover, information on the application, code of practices, duration, and frequency of the use of organophosphate and carbamate pesticides was obtained from questionnaires and analyzed by using descriptive statistics and correlation coefficients. The results showed that 37.3% had AChE levels lower than standard (< 87.5 units/ml) indicating a risk to health (28.8%) and an unsafe condition (8.5%). The use of chemical pesticides was related to the AChE levels of farmers as follows: methods of uses (r = 0.452, p < 0.001), practice (r = 0.396, p < 0.001), duration (r = 0.206, p < 0.004), chemical content (r = - 0.243, p < 0.001), frequency (r = - 0.210, p < 0.001) and chemical type (r = 0.171, p < 0.001). While 80.9% of farmers used the pesticides in both groups, most farmers (76.7%) used the labeled instruction incorrectly by overusing the chemical pesticides, followed by wrong practices (53%), application (51.3%), duration (39.4%), and frequency (39.4%). The results of the AChE levels of farmers were 62.7% within standard (≥ 87.5 units/ml) which were considered safe levels.However, in order to be safe, farmers should strictly follow the instructions on the label/packaging of chemicals for application procedures and use personal protective equipment regularly. Especially, the farmers who had AChE levels lower than standard.